Empirical research of accounting conservatism, corporate governance and stock price collapse risk based on panel data model. Issue 4 (2nd October 2021) - Wang, Qian; Li, Xiang; Liu, Qiaoying
Abstract : This paper selects the panel data of the main board listed companies in Shenzhen and Shanghai from 2011 to 2016 as the research object and constructs the intersection of corporate governance comprehensive index and accounting conservatism and corporate governance index. Based on this, the mixed utility model is used to empirically test the relationship between accounting conservatism, corporate governance, and stock price collapse risk. The results show that: accounting conservatism, corporate governance and stock price collapse risk are negatively correlated, and conservative accounting policies can effectively restrain the occurrence of the stock price collapse, and higher levels of corporate governance can effectively reduce the possibility of the future stock price crash, and accounting conservatism and corporate governance have substitution effects in preventing the risk of the stock price collapse, and higher corporate governance levels can significantly reduce the negative impact of accounting conservatism on future stock price collapse risks. This paper also puts forward some suggestions to reduce the risk of stock price collapse from two aspects of improving accounting conservatism and strengthening corporate governance, which can be used as the reference for the sustainable and stable development of the capital market.